Answer:
Step-by-step explanation:
y = 2x - 1
y = x - 8 ------ (i)
substitute y = 2x - 1 in equation (i)
2x - 1 = x - 8
2x = x - 8 + 1
2x = x - 7
2x - x = -7
x = -7
Substitute x value in equation (i)
y = -7 - 8
y = -15
Nlaleicodklqjdixkzkxknc uv
5x + 60y = 35
x +y = 1.5 : rewrite as x = 1.5-y and substitute this formula for x in the first one:
5(1.5-y) + 60y = 35
distribute:
7.5 - 5y + 60y = 35
combine like terms:
7.5 + 55y = 35
subtract 7.5 from both sides:
55y = 27.5
divide both sides by 55 to solve for y
y = 27.5 / 55 = 0.5
now substiute 0.5 for y in the 2nd equation:
x + 0.5 = 1.5
x = 1.5 - 0.5 = 1
he walked for 1 hour
It equals to the the w-4 that’s allows you that will the net pay in your paycheck
Answer:
x = 12
Step-by-step explanation:
Complementary angles add up to have a sum of 90 degrees. We can create an equation and solve for x.
3x + 6x - 18 = 90
~Simplify
9x - 18 = 90
~Add 18 to both sides
9x = 108
~Divide 9 to both sides
x = 12
Best of Luck!